Optimization Of Solder Paste Printing Parameters Using Design Of Experiments (DOE) - Sekharan, Gopal; Mohd. Rohani, Jafri; Mohd. Yusof, Sha'ri; Abu Bakar, Zailis (Penerbit UTM Press, 2005)
The Solder Paste Printing Process Is An Important Process In The Assembly Of Surface Mount Technology (SMT) Devices Using The Reflow Soldering Technique. There Is A Wide Agreement In The Industry That The Paste Printing Process Accounts For The Majority Of Assembly Defects. Experience With This Process Has Shown That Typically Over 60% Of All Soldering Defects Are Due To Problems Associated With The Screening Process. Therefore, Operation And Parameter Setup Of The Stencil Printing Process Are The Key Elements When Trying To Minimize Defects. Parameters Such As Squeegee Pressure, Squeegee Speed, Stencil Separation Speed, Snap-Off And Stencil Cleaning Interval Are The Most Important Factors In The Process To Achieve A Better Yield. This Paper Describes The Experiment Design Approach For Solder Paste Printing Process. A Factorial Design Technique Has Been Used To Study The Effects Of The Solder Paste Printing Process Parameters. Sixteen Experimental Trial Were Carried Out In The Experiment With Two Levels For Each Factor. The Output From The Experiment Is The Solder Paste Height, And The Data Has Been Statistically Analyzed By Using Minitab Software. The Analysis Of Variance (ANOVA) Showed That The Important Factors For The Solder Paste Height Are Squeegee Pressure And Snap-Off With The Optimal Setting For Printing Speed, Squeegee Pressure, Snap-Off, Squeegee Separation, And Cleaning Interval. The Experiment Error Between The Predicted Regression Model And Actual Verification Was Found To Be 1.61%. It Is Shown That By Using DOE 18% Improvement Of The Solder Paste Height Can Be Achieved.